MODIFIED HZSM-5 AND H-MORDENITE ZEOLITES AS SUPPORTS FOR PLATINUM CATALYST - Shanshool, Jabir; Al-Rawi, Usama A. S. (Nahrain University College of Engineering Journal, 2019)
Bifunctional Pt/HZSM-5 and Pt/HMOR catalysts were prepared and applied to the isomerization of n-Hexane. Catalysts containing 0.3wt% Pt on both catalysts with potentially high acidity were prepared by impregnation method. The tested catalysts show that optimum selectivity with maximal isomer yield was obtained for Pt/HZSM-5 catalysts. The nanoparticles were characterized by inductively coupled Plasma (ICP), X-Ray Diffraction (XRD), BET Surface Area, andTransmission Electron Microscopy (TEM). TEM was revealed uniformly dispersed platinum particles on the substrate with average particle size ranging from ~6.893 to 8.847nm. It was demonstrated that the loading content and particle size of the nanoparticles deposited on zeolites could be tuned bychanging the weight of precursor and the conditions of loading